Multi-ramp reference voltage PWM imaging scheme with enhanced dynamic range and correlated double sampling. (November 2017) - Gao, Zhiyuan; Zhou, Yiming; Xu, Jiangtao
Abstract: A multi-ramp reference voltage readout scheme for CMOS digital pixel sensor (DPS) based on pulse width modulation (PWM) imaging is proposed to extend the dynamic range (DR) and eliminate the fixed pattern noise (FPN). The exposure period is divided into two sampling stages, the FPN and some random noise can be eliminated by time-domain correlated double sampling (CDS). The multiple ramps are introduced to obtain a larger DR although the integration time is limited. A behavioral model of the PWM DPS with this scheme is simulated with MATLAB, the DR, photoresponse and FPN are analyzed versus the design parameters. A DPS with the multi-ramp reference can achieve 103.06 dB DR with CDS at 100fps, 16-bit memory depth and 1.8 V power supply. And the DR can be further extended to 138.49 dB with a single sampling at high light condition. FPN can drop to less than 1LSB after the CDS operation from 3.97% without CDS.